The Wiley handbook on violence in education forms, factors, and preventions - Shapiro, Harvey (Wiley handbooks in education, 2018)
In this comprehensive, multidisciplinary volume, experts from a wide range fields explore violence in education's different forms, contributing factors, and contextual nature.